PENGARUH PERCEIVED VALUE TERHADAP CUSTOMER LOYALTY YANG DIMEDIASI OLEH CUSTOMER SATISFACTION SUNSCREEN NIVEA DI KOTA BANDUNG - Lestari, Pena; Tania Adialita (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This study aims to analyze the effect of perceived value on customer loyalty mediated by customer satisfaction for Nivea sunscreen consumers in Bandung City. The sampling technique used convenience sampling and determined 90 people as respondents. The process of obtaining primary data through questionnaires to Nivea sunscreen users aged 17 years and over and secondary data obtained from Topbrandaward 2023. The data were analyzed through reliability tests, validity tests, classical assumption tests, simple and multiple regression tests, hypothesis tests and sobel tests. The findings state that perceived value has a positive and significant effect on customer satisfaction and customer loyalty of Nivea sunscreen in Bandung City. In addition, customer satisfaction can act as a mediator between perceived value and customer loyalty of Nivea sunscreen in Bandung City. Keywords: Perceived Value, Customer Satisfaction, Customer Loyalty